REASONS FOR THE INCREASE IN ANTIBIOTIC RESISTANCE OF MICROORGANISMS (INTERNATIONAL CONFERENCE ON MEDICINE, SCIENCE, AND EDUCATION, 2026)
According to the World Health Organization (WHO), more than 700,000 people die each year due to antibiotic-resistant infections. It is estimated that by 2050, this figure could reach 10 million. This poses a massive threat to the global community, not only medically but also socio-economically. Antibiotic resistance negatively impacts the reliability of healthcare systems, the duration of disease treatment, and overall healthcare costs.